Formação e identidade do professor tutor no ensino superior na modalidade a distância: a produção de teses e dissertações brasileiras na área de educação (2001 - 2010) - Palermo, Roberta Rossi Oliveira (2013)
This research work aims to elaborate a ponderation of the production of Brazilian dissertations and thesis under the theme formation and identity of the tutor teacher in Superior Education at distance, considering the period from 2001 to 2010, after the promulgation of the Law n. 9394/96, which determines the guidelines of the national education!and!increases!the!conception!of!teachers !initial!and!continued!formation,!and!also! creates the possibility of regular distance courses that bring the central figure of the tutor teacher. It is bibliographical research accomplished with the theoretical support of authors such as C. Dubar, C. Marcelo Garcia, D. Vaillant, M. Tardif and D. Raymond. We identify and characterize the group of research under these themes, as well as investigate the perspectives of analysis presented in the selected works, defining tutor teacher, his/her formation and his/her performance, considering the different models of distance education. The investigation was accomplished by means of mapping the academic production at the Bank of Dissertations and Thesis at CAPES Coordination! of! People s! Improvement! at! Superior Education, from 2001 to 2010 production available at: http://www.capes.gov.br/servicos/banco-de-teses, using the following descriptors: identity / formation / tutor teacher / distance learning. The group of research located and selected was analysed with the aid of an Analysis Guide previously built and tested. The data obtained was organized in synthesis charts, graphs and tables and allowed us to gather elements to the understanding of aspects such as: the relation between the personal/professional profile and the! tutor s! performance;! the! identity!with! the! profession! and! the! appreciation! of! the! tutor s! function as a teaching work as decisive factors to the quality of his/her acting; the distance learning!models!as!determinants!of!the!tutor s!collective!and!individual!identity;!the!teaching! formation has not been condition to the tutor s!performance,!reducing!his/her!formation!to!a! in-service preparation, based on rules and procedures that organize his/her actions, or to a self-formation; and, finally, the configuration of a new feature of the teaching profession at distance, with the! identification!of!distinctive! teaching!knowledge,!due! to! the! tutor! teacher s! performance